2016
DOI: 10.1093/abbs/gmv122
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics-based identification of <italic>WRKY</italic> genes and characterization of a salt and hormone-responsive <italic>PgWRKY1</italic> gene in <italic>Panax ginseng</italic>

Abstract: WRKY proteins belong to a transcription factor (TF) family and play dynamic roles in many plant processes, including plant responses to abiotic and biotic stresses, as well as secondary metabolism. However, no WRKY gene in Panax ginseng C.A. Meyer has been reported to date. In this study, a number of WRKY unigenes from methyl jasmonate (MeJA)-treated adventitious root transcriptome of this species were identified using next-generation sequencing technology. A total of 48 promising WRKY unigenes encoding WRKY p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 66 publications
0
18
0
1
Order By: Relevance
“…This suggests that PgWRKY1 might be a multiple stress‐inducible gene that can respond to hormones and salt stress, and may also be important for root formation (Nuruzzaman et al . ). On the basis of these reports, we suggest, JrWRKY2 and JrWRKY7 are important candidate genes in abiotic stress responses, tissue formation and development.…”
Section: Resultsmentioning
confidence: 97%
“…This suggests that PgWRKY1 might be a multiple stress‐inducible gene that can respond to hormones and salt stress, and may also be important for root formation (Nuruzzaman et al . ). On the basis of these reports, we suggest, JrWRKY2 and JrWRKY7 are important candidate genes in abiotic stress responses, tissue formation and development.…”
Section: Resultsmentioning
confidence: 97%
“…Nuruzzaman et al. obtained 48 transcription factors related to the ginsenoside synthesis by transcriptional sequencing of the adventitious roots treated with MJ, in which the transcription factors of WRKY1‐9 were identified. In addition, it was found that WRKY1‐9 had different expression levels in roots, stems, leaves, adventitious roots, and seeds.…”
Section: Regulation Of Ginsenoside Biosynthetic Pathwaymentioning
confidence: 99%
“…达 玛烷合酶(dammarenediol synthase, DS)可催化2,3-氧化 鲨烯生成达玛烯二醇, 被认为是人参皂苷生物合成中 最重要的关键酶, Han等人 [36] 通过RNAi技术使DS基因 沉默, 导致人参根中皂苷含量降低至对照组的84.5%. 可响应SA, ABA和NaCl的正向调控, 表明其可能参与 人参的多个信号途径 [99] .…”
Section: 基因抑制 鲨烯经Se的作用生成23-氧化鲨烯unclassified